Sustainable Development Goals in International Law: A review of challenges in Implementation and Integration - Albakjaji, Mohamad (Journal of Posthumanism, 2025)
The challenges of integration and implementation of sustainable development goals in international law are complex and multifaceted, arising from both the broad scope of sustainable development goals (SDGs) and the inherent limitations of legal frameworks. Theoretically, economic growth, social equity, and the protection of the environment are the main elements of sustainable development. However, achieving the balance between these goals is challenging on a global level. This paper aims to explore the main challenges that may face the incorporation of SDGs in international law and to study the main reasons and factors that affect the implementation of sustainable development goals in international law. The research finds that there are some factors that hinder the implementation and enforcement of the sustainable development goals internationally. One of the main issues is the nature of sustainable development as an "obligation of means" rather than an "obligation of result". International law does not require states to guarantee the achievement of SDGs but to make efforts towards it. The fragmented nature of sustainable development goals, the lack of binding agreements, competing national interests and the issue of Cherry-Picking in Implementation result in creating room for variability in commitment and enforcement.